Penguatan Entrepreneurial Mindset Siswa SMA Darul Hikam lewat Simulasi BMC - Suryono, Herdiansyah Gustira Pramudia; Silvianita, Anita; Hadiansah, Ihsan; Pringgabayu, Dematria (Apik Cahaya Ilmu, 2025)
The high rate of youth unemployment and the limited integration of entrepreneurship education in secondary schools present a serious challenge in preparing young generations to become independent and adaptable to future economic dynamics. This community engagement program aimed to foster an entrepreneurial mindset and equip students of SMA Unggulan Darul Hikam with fundamental skills in designing business models using the Business Model Canvas (BMC) approach. The method applied was experiential learning through participatory workshops, which included theoretical sessions, BMC simulations, group presentations, and pre-test and post-test evaluations. The results showed a significant improvement in students’ understanding of entrepreneurship concepts and the key elements of the BMC framework. All student groups successfully completed their business model designs and presented relevant and contextually appropriate business ideas. In addition to cognitive gains, the training also enhanced participants’ collaboration, communication, and self-confidence. Feedback from students indicated a high level of enthusiasm and expressed hope for continued support through mentoring and the replication of similar workshops in other schools. The program concludes that BMC is an effective method for entrepreneurship education among adolescents and holds great potential to be integrated into school curricula or character development programs focused on entrepreneurship at the secondary level